Aridity, fire severity and proximity of populations affect the temporal responses of open-habitat birds to wildfires. (August 2022) - Puig-Gironès, Roger; Brotons, Lluís; Pons, Pere
Abstract: The loss of open habitats in Europe has led to severe declines in birds associated with these habitats. However, certain ecological disturbances reverse the trend towards afforestation and create appropriate conditions for open-habitat species. Yet, open-habitat bird occupancy dynamics after disturbance depend on a complex combination of as-yet poorly studied factors. We analysed the colonization patterns and post-fire time-window of occurrence of open-habitat species along 687 transects in 68 burnt areas over a period of 11 years. During the study, 8345 individuals belonging to 22 open-habitat birds were detected. Species richness was related to an increased time elapsed since the fire, fire severity and proximity of potential population sources. Many species changed across the 11 years post-fire. Some species like the tawny pipit and the ortolan bunting, showed time lags affecting the timing of local extinction. Water deficit played a significant role in bird occurrence and six species benefited from drier conditions. Open-habitat species were more frequently detected in burnt areas near previously occupied areas and in severely burnt areas. Our results support the hypothesis that fire plays a critical role in the distribution dynamics of open-habitat species. Peak number of species was reached rapidly, between two and 6 years after fire, although a few species showed their peak abundance later on. An appropriate strategy for favouring open-habitat specialists in these landscapes, while reducing the risk of large wildfires, should prioritize integrated fire management to generate patches of different fire ages. Graphical abstract: Unlabelled Image Highlights: Open-habitat species are overrepresented on the lists of threatened European birds. Wildfires generate appropriate local conditions for open-habitat bird species. Open-habitat birds occurred more frequently in severely burnt areas and near previously occupied areas. Open-habitat species richness peaked between two and 6 years after fire. Integrated fire management can favour open-habitat bird specialists in Mediterranean landscapes.